ARTIFICIAL INTELLIGENCE IN MARKETING: NEW METHODS - Makhmudjan Mukhamedjanovich Ikramov (Web of Journals Publishing, 2023)
In the article, the author outlines the degree of influence of artificial intelligence on the economy and business, and also examines its opportunities and problems.
Keywords: artificial intelligence, algorithm, data, machine learning, transaction, digital economy.